1997
DOI: 10.1016/s0014-5793(97)00874-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired expression of transcription factor IUF1 in a pancreatic β‐cell line derived from a patient with persistent hyperinsulinaemic hypoglycaemia of infancy (nesidioblastosis)

Abstract: Persistent hyperinsulinaemic hypoglycaemia of infancy (PHHI), or nesidioblastosis, is a rare disorder which may be familial or sporadic, and which is characterized by unregulated secretion of insulin and profound hypoglycaemia in the neonate. The defect has been linked in some patients to mutations in the sulphonyl urea receptor gene (SUR). The present study investigated potential defects in the regulation of the insulin gene by glucose in a P-cell line (NES 2Y) derived from a patient with PHHI. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 31 publications
(43 reference statements)
1
69
0
Order By: Relevance
“…MIN6 ␤ cells (27) (passages [19][20][21][22][23][24][25][26][27][28][29][30] were grown in DMEM containing 15% FCS, 25 mM glucose, 5.4 mM KCl, 2 mM glutamine, 100 mM 2-mercaptoethanol, 100 units͞ml Ϫ1 penicillin, and 100 g͞ml Ϫ1 streptomycin in a humidified atmosphere at 37°C with 5% CO 2 , and seeded onto poly(L)-lysinecoated coverslips for microinjection. Cells were transfected with Lipofectamine 2000 or TransIT-TKO (for siRNA).…”
mentioning
confidence: 99%
“…MIN6 ␤ cells (27) (passages [19][20][21][22][23][24][25][26][27][28][29][30] were grown in DMEM containing 15% FCS, 25 mM glucose, 5.4 mM KCl, 2 mM glutamine, 100 mM 2-mercaptoethanol, 100 units͞ml Ϫ1 penicillin, and 100 g͞ml Ϫ1 streptomycin in a humidified atmosphere at 37°C with 5% CO 2 , and seeded onto poly(L)-lysinecoated coverslips for microinjection. Cells were transfected with Lipofectamine 2000 or TransIT-TKO (for siRNA).…”
mentioning
confidence: 99%
“…25 The passage of the cells occurred over 15 stages and this cell line had the crucial characteristics of being able to grow in culture but contained defective potassium channel expression indicative of the original disease; thus was not glucose responsive. Therefore, we considered this to be an appropriate candidate for producing functional β-cell hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 In 1997 Macfarlane et al described the derivation of a human insulin-producing cell line, which showed defective potassium channel expression and was not glucose responsive but, crucially, had characteristics of being able to grow in culture. 25 In this work, flow cytometric analysis was carried out to examine the intracellular hormone and other endocrine cell-related antigenic expression of NES2Y cells from primary culture. The results showed that the NES2Y cells exhibited an endocrine phenotype with continuous culture over 2, 4, 6 and 8 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations